The fourth closet - Cawthon, Scott 1971-; Breed-Wrisley, Kira (Cawthon, Scott 1971- Five nights at Freddy's, 2018)
What really happened to Charlie? Meanwhile, there's a new animatronic pizzeria opening in Hurricane, along with a new rash of kidnappings that feel all too familiar. Bound together by their childhood loss, John reluctantly teams up with Jessica, Marla, and Carlton to solve the case and find the missing children. Along the way, they'll unravel the twisted mystery of what really happened to Charlie, and the haunting legacy of her father's creations